FROM HAE CHAN TO HAIKAL: LOCALIZATION OF K-POP IDOL NAMES IN TWITTERATURE - Naura Mukti Larasati; Amala Nadhifa; Amanda Putri Vebya; Pyeonggang, Choi (CrossOver, 2024)
Alternate Universe (AU) on Twitter employs public figures such as K-pop idols as characters and localized their names. K-pop idols already possess global appeal, but localization helps integrate these figures into regional or cultural contexts, making stories resonate deeply with local audiences. Name localization in this context is about adapting names to fit different languages and cultures. This research aims to investigate the localization of a K-pop idol’s names in the context AU based Twiterrature in X platform, formerly Twitter. The focus is to see how localization of K-pop idol names is applied in Twitterature, addresses a significant gap in existing studies by exploring the intersection of localization strategies. To analyze it we used localization based on Lyons (1977), the idea that spatial expressions are more essential, grammatically and semantically than non-spatial expressions. In this context, spatial expressions are the different strategies used to localize each K-pop generation. In order to localize, name translation could be expressed through aleatory and intentional techniques. To analyze the data we used Spradley 4 step technique; domain analysis, taxonomy analysis, componential analysis, and cultural theme analysis. The primary findings in this research indicate that the author's choice of names was frequently influenced by random or arbitrary factors rather than a systematic or thematic rationale. This study aims to enhance understanding of how localization strategies function in Twitterature, specifically in adapting global cultural figures like K-pop idols into localized and culturally relevant stories.